1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Expectation of position and momentum at time t, pictures

  1. Dec 3, 2015 #1
    1. The problem statement, all variables and given/known data

    Consider a particle, with mass m, charge q, moving in a uniform e-field with magnitude E and direction X_1.

    The Hamiltonian is (where X, P, and X_1 are operators):

    The initial expectation of position and momentum are <X(0)> = 0 and <P(0)>=0

    Calculate the expectation of position and momentum oprator in the Schrodinger picture is X (t) = (X_1, X_2, X,3)

    2. The attempt at a solution

    I know the Hamiltonian and the initial condition. I am doing this in the schrodinger picture, and that with the time evolution operator I can represent the ket as

    |phi(t)> = U (t,0) |phi(0)>

    Is H is time-independent? As P is squared and is the magnitude of the P? If so the time evolution operator can be represented as

    U (t,0) = exp (-i*t*H/hbar)


    I can represent phi(t) in terms of those terms and phi(0) and proceed but I am not sure if that is correct.

    I know that P = mv = m dx/dt so I think I can use the derivative of the expectation value of X when I get that, correct. According to the equation:

    d/dt <O>_t = i/h <[H,O]>_t + <dO/dt>_t

    but I have to find the expectation of the position first.

    Any help would be much appreciated!
  2. jcsd
  3. Dec 3, 2015 #2


    User Avatar

    Staff: Mentor

    You don't need to know φ(t).

    That should not be necessary.

    Start with that equation, and see what you get for P and X.
  4. Dec 3, 2015 #3
    Okay, plugging X into that equation (get rid of _t for legibility) I get

    d/dt <X> = i/h <[H,X]> + <dX/dt>
    = i/h <[(P^2/2m - E*q*X_1), X]>+<dX/dt>
    = i/h (-E*q) <X,X1>+<dX/dt>

    and I'm not sure where to go from here...
  5. Dec 3, 2015 #4
    What if I just did:

    U (t,0) = exp (-i*t*H/hbar)
    = exp (-i*t*(P^2/2m - E*q*X_1)/hbar)

    |phi (t)> = exp (-i*t*(P^2/2m - E*q*X_1)/hbar) |phi(0)>

    <phi (t)|X|phi(t)> = <phi(0) exp (i*t*(P^2/2m - E*q*X_1/hbar) | X | exp (-i*t*(P^2/2m - E*q*X_1)/hbar) |phi(0)>

    but I don't know where I would go next, could I just multiply it in? But they are operators.
  6. Dec 4, 2015 #5


    User Avatar

    Staff: Mentor

    What is the commutator of X and P? What can you say about the time-dependence of an operator (not explicitly time dependent) in the Schrödinger picture?

    You can't go anywhere with that. Note also that you do not know what |φ(0)>, only that <φ(0)|X|φ(0)> = <φ(0)|P|φ(0)> = 0.
  7. Dec 4, 2015 #6
    I know that the commutator of x and p is i*hbar and that in the Schrödinger picture the operators are time independent
  8. Dec 4, 2015 #7


    User Avatar

    Staff: Mentor

    X1 is only one of the spatial dimensions (if I understand correctly "X (t) = (X_1, X_2, X,3)"), and p2 is simply pp, so
    [p^2,x] &= p^2x-xp^2 \\&= ppx - xpp \\
    &= ppx - xpp - pxp + pxp \\
    &= ppx - pxp + pxp - xpp \\
    &= p[p,x] + [p,x]p
  9. Dec 4, 2015 #8
    Ah ok so then, assuming that the commutator of x and x_1 is 0 I would get:

    d/dt <X> = i/h <[H,X]> + <dX/dt>
    = i/h <[(P^2/2m - E*q*X_1), X]>+<dX/dt>
    = i/h <[X*P^2/2m -X*P^2/2m]>+<dX/dt>
    = i/(2mh) <[X,P^2]>+<dX/dt>
    = i/(2mh) <2*i*h*p>+<dX/dt>
    = i/(2mh)*(2*i*h) <p>+<dX/dt>
    = -1/m<p> +<dX/dt>

    <p> = m (d/dt <X> - <dX/dt>)

    But that still has a lot of unknows for a final answer as I have to find out <X> as well
  10. Dec 4, 2015 #9
    If I did the same procedure for P then it would be

    d/dt <P> = i/h <[H,P]> + <dP/dt>
    = i/h <[(P^2/2m - E*q*X_1), P]>+<dP/dt>
    = i/h <[P*-E*q*X_1 -E*q*X_1*P]>+<dP/dt>
    = i(-E*q)/h <[P,X_1]>+<dP/dt>
    = i/(2mh) <i*h>+<dP/dt>

    But then if [P,X_1] = ih then this doesn't really make sense...
  11. Dec 5, 2015 #10


    User Avatar
    Science Advisor
    Homework Helper

    Sorry for butting in, just a short intervention to remind the OP that dX/dt = dp/dt = 0.
  12. Dec 5, 2015 #11
    Ah, thank you.

    So then

    <p> = m (d/dt <X>)


    d/dt <P>= i(-E*q)/h <[P,X_1]>

    Is that the final answer?
    The second portion of the question is to, with the same Hamiltonian, knowing that in the Heisenberg Picture , X_H = (X_1H,X_2H,X_3H), find the commutator

    [X_aH (t), X_bH (0)]

    where all the X are operators

    I know that in the Heisenberg picture the operators evolve with time as U^+ (t,0) O U(t,0)
    Last edited: Dec 5, 2015
  13. Dec 6, 2015 #12
    So then for the heisenberg picture, because e^(0) = 1 and thus for X_bH (0), U would equal 1. I would get (where U_d represents U dagger)

    U_d X_aH U X_b - X_b U_d X_aH U

    then I don't know what to do
  14. Dec 6, 2015 #13


    User Avatar
    Science Advisor
    Homework Helper

    No, you still have to solve those two coupled differential equations.
  15. Dec 6, 2015 #14
    ah, okay. Plus I still need to find <[P,X_1]> right. Could you help me with that commutator?

  16. Dec 6, 2015 #15


    User Avatar
    Science Advisor
    Homework Helper

    Is P actually a vector in your notation? Is it actually ##\mathbf{P} = P_1\hat{i} + P_2\hat{j} + P_3\hat{k}##?
  17. Dec 6, 2015 #16
    It doesn't specify but I would assume it is a vector
  18. Dec 6, 2015 #17


    User Avatar
    Science Advisor
    Homework Helper

    In that case, it will be ##[P_1\hat{i} + P_2\hat{j} + P_3\hat{k},X_1] = [P_1,X_1]\hat{i} + [P_2,X_1]\hat{j} + [P_3,X_1]\hat{k}##. You know the value of each term, don't you?
  19. Dec 6, 2015 #18
    Yes so then it would just be [P,X_1] = ih ?

    Then the equation would be, as I put in post 9

    d/t <P> = = i/(2mh) <i*h>
  20. Dec 6, 2015 #19


    User Avatar
    Science Advisor
    Homework Helper

    Don't forget the unit vector, ##[P,X_1] = i\hbar\hat{i}##.
    That equation will then disperse into three equations, each for the momentum components and it should be easily solvable.
  21. Dec 6, 2015 #20
    As ih is a constant wouldn't <ih> just be equal to ih since the exponentials of the U term would become 1 and the phi(0) would as well.

    And then I could sub in the first equation to get the value for <x>?
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted